1993
DOI: 10.1161/01.res.72.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation of angiotensin converting enzyme activity and mRNA levels by angiotensin II.

Abstract: Although renin and angiotensinogen are known to be subject to feedback regulation, the effects of angiotensin II (Ang II) on the regulation of angiotensin converting enzyme (ACE) gene expression and enzymatic activity have not yet been studied. Therefore, the effects of exogenous Ang II infusion and ACE inhibition on ACE mRNA expression were examined. Ang II was infused intravenously in male Sprague-Dawley rats for 3 days at 100 (low dose), 300 (medium dose), or 1,000 (high dose) ng/kg per minute (n = 8 for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 41 publications
3
58
1
1
Order By: Relevance
“…11,26 Renin is activated during long-term ACE inhibitor therapy, and AngI levels are elevated. 6,7 The increased substrate levels may therefore be adequate to overcome the competitive inhibition of the converting enzyme, especially during the intervals between dosing. In addition, tissue levels of AngII could persist even if circulating levels of the hormone are suppressed by the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,26 Renin is activated during long-term ACE inhibitor therapy, and AngI levels are elevated. 6,7 The increased substrate levels may therefore be adequate to overcome the competitive inhibition of the converting enzyme, especially during the intervals between dosing. In addition, tissue levels of AngII could persist even if circulating levels of the hormone are suppressed by the drug.…”
Section: Discussionmentioning
confidence: 99%
“…5 ACE inhibitors are also competitive inhibitors whose blockade could be overridden by increased AngI levels that result from the loss of feedback inhibition of renin activity. 6,7 Even if circulating AngII levels are reduced, the ability of different ACE inhibitors to suppress various tissue levels of AngII remains unclear. 8 Furthermore, there is growing evidence that alternative pathways of conversion of AngI to AngII, including a chymase pathway, may restore circulating or tissue levels despite ACE inhibition.…”
mentioning
confidence: 99%
“…27 Moreover, TACE in these latter models was not subject to feedback regulation by Ang II, as is the case for endothelial ACE. 70 Myocardial ACE activity, measured by the conversion of Ang I to Ang II in isolated perfused rat heart, is increased after suprarenal aortic banding. 71 This may be related to increased TACE that accompanies the perivascular fibrosis of intramyocardial coronary arteries in both ventricles with RAAS activation.…”
mentioning
confidence: 99%
“…Notably, chronic use of chemical ACE inhibitors can also increase ACE mRNA level in heart, lung, duodenum, and aorta by feedback regulation. 30,34,35 We found that ACE mRNA expression measured by RT-PCR did not increase in the myocardium immediately after ischemia/reperfusion. Pretreatment with captopril also did not affect the level of ACE mRNA in myocardium.…”
Section: Discussionmentioning
confidence: 77%